Gambaran Tingkat Stres Mahasiswa Semester 2 Keperawatan Yang Praktik Klinik di RS Santa Elisabeth Medan - Gryttha Tondang; Indra Hizkia; Magda Siringo Ringo; Bernadetta Ambarita; R Oktaviance S (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Stress is a common condition experienced by nursing students during clinical practice. In the early stages of clinical practice, second-semester students generally experience anxiety, low self-confidence, and pressure from academic demands and the hospital environment. High levels of stress can impact learning motivation, practical skills, and even students' mental health. Stress is an emotional and physiological response when an individual feels an imbalance between the demands faced and their abilities. Every nursing student is susceptible to stress during clinical practice, influenced by several factors, such as a heavy academic load, interactions with patients and their families. This stress, if not managed properly, can result in decreased concentration, decreased academic performance, mental health disorders, and reduced quality of nursing services provided. The phenomenon of stress in nursing students does not only occur in Nursing students at the Santa Elisabeth Medan Health Sciences College. The research method used a descriptive design with a cross-sectional approach. The study population was 139 second-semester students, all of whom were used as the research sample (total sample). The data collection instrument used the Perceived Stress Scale (SPSS-24) questionnaire. Data were analyzed univariately and presented in the form of a frequency distribution. The results showed that the majority of students experienced moderate stress (97 people (69.8%), severe stress (36 people (25.9%), and low stress (6 people (4.3%). The conclusion of this study is that the majority of second-semester students experienced moderate stress, with a significant number experiencing severe stress.